PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK MENINGKATKAN MINAT BACA PADA MATA PELAJARAN SEJARAH MELALUI MATERI KEDATANGAN JEPANG KE INDONESIA KELAS XI SMA NEGERI 8 KOTA JAMBI - Septyana, Sakinah; Azmi, Ulul; Agustiningsih, Nur (Universitas Batanghari Jambi, 2025)
This research and development was raised from the problems that emerged in SMA Negeri 8 Jambi City, namely there are still the same learning media, the teaching materials used are still using printed books and LKS and teachers teach using lecture and PPT learning methods. This research has the aim of how to develop and feasibility of animation-based audio-visual media. The development model used is ADDIE which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The developed media was then validated by media experts and material experts. In the field trial, three stages of research were carried out, namely one-to-one trials obtained a score of 74.66% in the